Pengendalian Persediaan Obat Kemoterapi Melalui Pendekatan Analisis ABC Indeks Kritis di Ruang Pencampuran Instalasi Farmasi RSUP Dr. Mohammad Hoesin Palembang Tahun 2015 - Khuriyati, Layla Izzatul (UI Scholars Hub, 2016)
One of the featured services at RSMH is integrated chemotherapy services. One of the resources in support of these services is a pharmaceutical supplies including the Chemotherapy drugs are relatively expensive. In conducting the inventory control Dr. Mohammad Hoesin Hospital not classify drugs based on user value, investment value and criticality of drugs through certain methods. So in this study aims to conduct chemotherapy drug control approach ABC Analysis Critical Index in the Cytostatica Handling Room of Pharmacy Instalation RSUP Dr. Mohammad Hoesin Palembang. This study design using operational research with quantitative and qualitative descriptive analysis. The results showed that out of 83 drug items, for group A (60% -30% -10%) is a Paxus 100 mg injection. with an investment of IDR. 3,220,525,650, - of the total investment of IDR. 33,509,826,356, -.Critical Index Analysis group A (70% -20% -10%) with an investment of IDR. 11,045,150,780, - of the total investment value of IDR 33,509,826,356, - consists of six types of items, namely: Holoxan 1 gram injection, Leocovorin injection, doxorubicin 50 mg injection, Brexel 20 mg injection, Brexel 80 mg injection and Paxus 100 mg injection. While the group A (80% -10% -10%) or IDR. 12,472,877,428, - of the total investment value of IDR. 33,509,826,356, - consists of eight items, namely: Carboplatin 150 mg injection, Holoxan 1 gram injection, Leocovorin injection, doxorubicin 50 mg injection, Brexel 20 mg injection, 80 mg injection Brexel and Paxus 100 mg injection, and Taxotere 20 mg injection. Critical Index ABC Analysis method can assist the hospital in a drug needs planning to consider: consumption, investment value, the criticality of drugs for hospital cost efficiency.